An integrated strategy using LC-MS/MS combined with in vivo microdialysis for the simultaneous determination of lignans of Schisandra chinensis (Turcz.) Baill. Fructus and endogenous neurotransmitters: application in pharmacokinetic and pharmacodynamic studies. Issue 19 (2nd September 2021) - Fu, Jun; Zhang, Hongxu; Liu, Shu; Wu, Jiajie; Zhang, Yuying; Gao, Yang; Song, Fengrui; Qin, Yuhua; Hu, Xiuli; Liu, Zhongying
Abstract : A schematic diagram of the systematic strategies for pharmacokinetic and pharmacodynamic studies of SCF in the treatment of AD. Abstract : Schisandra chinensis (Turcz.) Baill Fructus (SCF) is the ripe fruit of Schisandra chinensis (Turcz.) Baill, and is often used as a neuroprotective drink. Modern pharmacological studies have shown that lignans are the main bioactive components responsible for neuroprotection and have potential in the treatment of Alzheimer's disease (AD). However, the mechanism of action of SCF in the treatment of AD from the pharmacokinetics–pharmacodynamics (PK–PD) perspective remains not well established. The purpose of this study is to investigate and compare the pharmacokinetic differences of lignans in normal and AD rats, as well as to investigate their effects on neurotransmitters and their role in the treatment of AD. To achieve this goal, an integrated strategy using LC-MS/MS combined with in vivo microdialysis for the simultaneous determination of lignans of SCF and endogenous neurotransmitters has been developed and validated. The results show that the pharmacokinetic behaviors of ten lignans in the AD group were significantly different from those in the normal group. The AD group had better absorption and slower elimination than the normal group. In addition, the pharmacodynamic results of the Morris water maze (MWM) test, biochemical tests, histopathological examination, as well as immunohistochemistry analysis showed that lignans could improve the learning and memory of AD rats. The oral administration of SCF could restore the levels of the neurotransmitter parameters; seven neurotransmitters showed clockwise or counterclockwise changes with the four lignans in the hippocampal region. Taken together, the PK and PD studies based on in vivo microdialysis sampling might offer novel insights into the mechanisms of action of SCF against AD.